SUPERIORITY OF ELLE WOODS IN AMANDA BROWN'S LEGALLY BLONDE MOVIE DIRECTED BY ROBERT LUKETIC: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - PARANINDITA, HERA DESSY (2011)
The major problem of this study is how superiority of Elle Woods reflected in the major character's personality. The objective of the study is to analyze the movie based on structural elements and to analyze superiority of Elle Woods based on an individual psychological approach. This study focuses on the major character, namely Elle. The benefit of this study is to give additional information which can be used by the other literature researcher who are interested in analyzing this play. This study uses two data sources, namely primary and secondary data source. The primary data source is the movie itself, Legally Blonde by Robert Luketic, while the secondary data taken from some information needed. The method of data collection method. Based on the analysis, the writer concludes that superiority of Elle Woods in Legally Blonde is influenced by some aspect. They are fictional finalism, inferiority feeling, striving for superiority, style of life, social interest and creative power. The six elements above have closed relationship. Elle Woods has goal to find her love. Warner Hummington. She is affraid loosing all of her memories with Warner Hummington, until she want to go to Harvard Law School to get her love back. She is striving for superiority, has a useful social type, high social interest and she has creative power. All of six elements above are needed for Elle Woods for getting her goal. Based on An Individual Paychological aspect shown in the film., the writer then concludes that literary work reflects the condition of people who has a dream or goal and they struggle to get it.